IMPLICATIONS OF SHARIA TOURISM FOR INCREASING INCOME AND PUBLIC WELFARE - Pakhrorrozi Pakhrorrozi; Hanif Ahmad Widianto (STIESA Press, 2020)
Tourism is one of the sectors that contribute in improving the economy of a country. Currently, tourism is becoming a trend of sharia tourism in which its operation in accordance with Islamic sharia. The existence of a new sector of sharia tourism is expected to have an impact on the increase in income and welfare of the community. The level of people›s welfare is measured by how much income levels are earned. This study aims to determine the impact of the existence of Islamic tourism to increase income and welfare of society in Lombok by using qualitative research methods. From the results of research conducted in the Department of Tourism and tourist sites by using three techniques of data collection that is observation, interviews, and documentation can be concluded that overall Islamic tourism has a positive impact on the increase of income society and affect the welfare of the community it self.